ETHICAL LEADERSHIP AND ITS IMPACT ON ORGANIZATIONAL COMMITMENT AND PERFORMANCE - Nur Aisyah; Ari Kristiana; Nur Afridah (CV. Adiba Aisha Amira, 2026)
Ethical leadership is becoming an important issue in modern organizations facing high performance demands as well as the need for integrity and sustainability. This study aims to comprehensively examine the concept of ethical leadership and its impact on organizational commitment and performance based on the results of previous research. The research method used is a literature review with a qualitative approach, involving the examination of reputable national and international journal articles, as well as relevant books and scientific publications. Data was collected by searching scientific databases such as Scopus, Google Scholar, and SINTA, and then analyzed using thematic and comparative analysis. The study results indicate that ethical leadership, characterized by integrity, fairness, responsibility, and transparency, has a positive influence on organizational commitment, particularly affective and normative commitment. Additionally, ethical leadership has also been shown to improve organizational performance both directly and indirectly thru increased employe motivation, trust, and commitment. This finding confirms that the implementation of ethical leadership is a strategic factor in sustainably improving organizational commitment and performance.